دور الاتصال التنظيمي في تحسين الصورة الذهنية للمؤسسة العمومية لدى جمهورها الداخلي - دراسة ميدانية ببلدية مداوروش - بوقفة سناء; شريط إكرام (My University, 2021)
Summary The study came to identify the role played by organizational communication in improving the mental image of the public institution. In this study, we have discussed the importance of organizational communication for public institutions and the municipality in particular, as well as the importance that various institutions attach to the mental image. The study relied on a major problem, which is what is the role of organizational communication in improving the mental image of the municipality of Madawroush among its internal audience. To gather more information on the subject, we used observation as a secondary tool, and to study this topic, we divided the study into four chapters: The first chapter, in which we dealt with the conceptual and methodological framework of the study, and the second chapter was about the nature of organizational communication, its characteristics, objectives and most important types, and The methods adopted in it, then the third chapter in which we touched on the mental image in the institution, its characteristics, its importance, the conditions and factors affecting its formation, down to its components and the most important types, then followed by the fourth chapter entitled the applied framework and its methodological procedures, in which we presented the most important data obtained from Unpacking the form and analyzing it statistically, then we reached a number of results: The most common form of organizational communication in the municipality is written communication. The importance of organizational communication for the municipality lies in maintaining its stability and sustainability. The relationship between organizational communication and lipid profile is positive. The obstacles that prevent the formation of a good mental image of the municipality are rumors. ------------------------------ ملخص جاءت الدراسة بهدف تحديد دور الاتصال التنظيمي في تحسين الصورة الذهنية للمؤسسة العامة. وناقشنا في هذه الدراسة أهمية الاتصال التنظيمي للمؤسسات العامة، والبلدية تحديدًا، والأهمية التي توليها مختلف المؤسسات للصورة الذهنية. وارتكزت الدراسة على إشكالية رئيسية، وهي: ما دور الاتصال التنظيمي في تحسين الصورة الذهنية لبلدية مدوروش لدى جمهورها الداخلي؟ لجمع المزيد من المعلومات حول الموضوع، استخدمنا الملاحظة كأداة ثانوية، ولدراسة هذا الموضوع، قسمنا الدراسة إلى أربعة فصول: الفصل الأول، تناولنا فيه الإطار المفاهيمي والمنهجي للدراسة، والفصل الثاني، تناول طبيعة الاتصال التنظيمي وخصائصه وأهدافه وأهم أنواعه، والأساليب المتبعة فيه، ثم الفصل الثالث، تناولنا فيه الصورة الذهنية للمؤسسة وخصائصها وأهميتها والشروط والعوامل المؤثرة في تكوينها، وصولًا إلى مكوناتها وأهم أنواعها، ثم الفصل الرابع، بعنوان الإطار التطبيقي وإجراءاته المنهجية، عرضنا فيه أهم البيانات التي تم الحصول عليها من تفكيك النموذج وتحليله إحصائيًا، وتوصلنا إلى عدد من النتائج: أن أكثر أشكال الاتصال التنظيمي شيوعًا في البلدية هو الاتصال الكتابي. وتكمن أهمية الاتصال التنظيمي للبلدية في الحفاظ على استقرارها واستدامتها. وتُعد العلاقة بين الاتصال التنظيمي ومستوى الدهون علاقة إيجابية. إن العوائق التي تمنع تكوين صورة ذهنية جيدة عن البلدية هي الشائعات.
Keywords: الاتصال التنظيمي، الصورة الذهنية، المؤسسة العامة